Health information triangulation: A complex and agentic practice among young parents. Issue 1 (2015) - Greyson, Devon
ABSTRACT: In situations of contested knowledge, information seekers may engage in triangulation practices in order to assess which information is right to meet their needs. Triangulation has been much discussed among researchers, but less so among lay populations. This poster presents results related to the triangulation practices of a group of young parents seeking health and parenting information in the Greater Vancouver region of Canada. Young mothers and fathers in this study described and demonstrated multiple types of triangulation in order to assess and make sense of both authoritative and non‐authoritative information. Seeking pathways were varied but could be classified as one of: a) escalating authoritativeness, b) second opinions, c) medical/non‐medical perspective, or d) inclusive triangulation. Engagement in triangulation practices was used both in deference to and as a mode of challenging medical authority. The dominant cultural emphasis on intensive parenting, coupled with widespread access to the Internet, made it possible and in some cases necessary for lay people to engage in "scientific" information practices such as triangulation.